#WayfairGate and the growth of sex trafficking panics across social media - Williamson, Sarah Hupp (Critical criminology, 2023)
Moral panics around the issue of sex trafficking are not new, as human trafficking itself has roots in the moral concern over the prostitution of white women. However, in modern times the growth of social media has enabled sex trafficking conspiracies to quickly emerge and easily spread. Scant literature has explored how social media now plays a role in generating moral panics around sex trafficking. This paper uses tweets about the #WayfairGate conspiracy as a case study to analyze this issue. Findings reveal that moral panics generated through social media still follow the basic elements of a moral panic. Themes of religion and patriotism are also found. Further, the use of technology enables the fast spread of misinformation, generates stereotypes about both sex trafficking and human trafficking more broadly, and acts as a gateway introduction to other conspiracies. Such conspiracies should not be dismissed as they have the ability to impact public opinion and shape policy.